Odpowiedzi

2009-04-06T19:45:26+02:00
4-[7x-(3x+2y-1)+(-6x-2y+3)] = 4-7x+(3x+2y-1)-(-6x-2y+3)=
4-7x+3x+2y-1+6x+2y-3=2x+4y
2009-04-06T19:46:55+02:00
4-(7x-3x-2y+1-6x-2y+3)= 4-(-2x-4y+4)= 4+2x+4y+4=2x+4y+8
2009-04-06T19:47:01+02:00
4-[21x²+14yx -7x +6x+2y-3]
84x²+56xy-28x+28x+8y-12
84x²+56xy-56x+8y-12
2009-04-06T19:47:08+02:00
4-[7x-(3x+2y-1)+(-6x-2y+3)] = 4-[7x-3x-2y+1-6x+2y-3] = 4-7x+3x+2y-1+6x-2y+3 = 2x+6
  • ango
  • Rozwiązujący
2009-04-06T19:49:17+02:00
4-[7x-3x-2y+1-6x-2y+3] =4-[-2x-4y+4]=4+2x+4y-4=2x+4y
2009-04-06T19:49:28+02:00
4-{ 7x-3x-2y+1-6x-2y+3} = 4-{-2x-4y+4} = 4+2x+4y-4=2x+4y